2014
DOI: 10.1007/s12275-014-3512-7
|View full text |Cite
|
Sign up to set email alerts
|

A protective role of methionine-R-sulfoxide reductase against cadmium in Schizosaccharomyces pombe

Abstract: The Schizosaccharomyces pombe cells harboring the methionine- R-sulfoxide reductase (MsrB)-overexpressing recombinant plasmid pFMetSO exhibited better growth than vector control cells, when shifted into fresh medium containing cadmium chloride (abbreviated as Cd). Although both groups of cells contained enhanced reactive oxygen species (ROS) and nitric oxide (NO) levels in the presence of Cd, ROS and NO levels were significantly lower in the S. pombe cells harboring pFMetSO than in vector control cells. Conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The trend of Cd accumulation in PDB in our research almost accords with that of Cihangir and Saglam’s report. The abilities of some filiform fungi, ectomycorrhiza, and yeast for TTEs removal from liquid and solid media have been confirmed [ 39 , 40 , 41 ]. It has been suggested that the hypha of P. pulmonarius MT might successfully be used in processes related to the removal and recovery of TTEs from aqueous pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…The trend of Cd accumulation in PDB in our research almost accords with that of Cihangir and Saglam’s report. The abilities of some filiform fungi, ectomycorrhiza, and yeast for TTEs removal from liquid and solid media have been confirmed [ 39 , 40 , 41 ]. It has been suggested that the hypha of P. pulmonarius MT might successfully be used in processes related to the removal and recovery of TTEs from aqueous pollutants.…”
Section: Discussionmentioning
confidence: 99%